2015
DOI: 10.1002/jmor.20437
|View full text |Cite
|
Sign up to set email alerts
|

The extracranial venous system in the heads of beaked whales, with implications on diving physiology and pathogenesis

Abstract: Beaked whales are a poorly known but diverse group of whales that have received considerable attention due to strandings that have been temporally and spatially associated with naval sonar deployment. Postmortem studies on stranded carcasses have revealed lesions consistent with decompression sickness, including intravascular gas and fat emboli. These findings have been supported by analyses of intravascular gas emboli showing composition dominated by nitrogen gas. To increase our understanding of the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…The acoustic tissues have significant macrovasculature (e.g. Costidis and Rommel, 2016), and it is hypothesized that these large vessels allow controlled flow of warmed blood to the acoustic fats to keep them in a constant phase for echolocation. Houser et al (2004) detected no metabolic activity in the acoustic tissues (a glucose analog was not taken up), which either means acoustic fat cells lack glucose transporters, or there is little direct exchange with the blood.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic tissues have significant macrovasculature (e.g. Costidis and Rommel, 2016), and it is hypothesized that these large vessels allow controlled flow of warmed blood to the acoustic fats to keep them in a constant phase for echolocation. Houser et al (2004) detected no metabolic activity in the acoustic tissues (a glucose analog was not taken up), which either means acoustic fat cells lack glucose transporters, or there is little direct exchange with the blood.…”
Section: %mentioning
confidence: 99%
“…One missing piece of this puzzle is an understanding of the tissues from which the melon and mandibular fats are derived, which might help to elucidate how the synthesis and storage of wax esters first occurred -and these may have different origins. For example, Fraser and Purves (1960) proposed that the intra-mandibular fat body may be a highly modified form of bone marrow, whereas Costidis and Rommel (2016) suggested that the extra-mandibular fat body may be modified blubber. This is an interesting question given that the suites of lipids present in all acoustic depots within an individual are very similar.…”
Section: Evolution Of the Systemmentioning
confidence: 99%
“…However, it should be noted that these larger vessels show distinct heterogeneity in their distributions within the acoustic fats. In beaked whales for example, the extensive venous plexus in the IMFB is limited to the periphery of the tissue, with much reduced vascularity in the center (through which sound likely passes to the ears; Costidis & Rommel, ). We sampled this center region for our study and show that this area can differ by twofold to threefold in the density of small vessels.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the acoustic tissues have the potential for increased blood flow. This is based on evidence from the arterial and venous anatomy of the jaw fats of beaked whales and bottlenose dolphins (Costidis & Rommel, 2012, 2016a, 2016bHouser et al, 2004). Specifically, the IMFB has a higher number of large vessels compared to the EMFB.…”
Section: Microvasculature and Implications For Diving Animalsmentioning
confidence: 99%
See 1 more Smart Citation